Responses of crop production and soil health to chemical nitrogen fertilization in a maize-wheat rotation system - Deng, Meihua; Ma, Hua; Sadeghpour, Amir; Yang, Guiling; Hu, Yan; Yang, Dong (Frontiers in Environmental Science, 2023)
Chemical nitrogen (N) fertilizer generally applied in a high rate to avoid N limitation and maximize crop yields. To test the effectsof chemical N fertilizer on crop production and soil health,athree-yr trial with six N treatments of urea and controlled-release fertilizerconducted in a maize (Zea mays L.)-wheat (Triticum aestivum L.) rotation systemin order to evaluate the effects of N fertilization (0-550 kg N ha-1) on maize and wheat production, soil health indicators, and soil bacterial community using 16S rRNA gene sequencing. The maximum crop yield and aboveground N uptake efficiency were achieved at the N application ratesof 150 kg N ha-1 for wheat and200 kg N ha-1for maize.After three crop seasons, the soil properties werealtered by N application rates.For each kg of N applied, soil pH linearly decreased in a rate of 0.0004-0.0012pH unit.The soil N (TN)and C (TC) content reached a higher stable situation when the cumulative N application a certain rate. However, the C/N ratiolinearly decreased by increasing the rate of N fertilizer. Consequently, N application significantly decreased soil bacterial diversity due to thedecrease of α-diversity indexes of Shannon and Pielou_eby increasingthe rate of N fertilization. At phylum, the chemical N application wassignificantly depleted by the members of Acidobacteria, Chloroflexi, andNitrospirae,but improved the growth of Actinobacteria,Gemmatimonadetes, Firmicutes, and Patescibacteria. Compared with urea,the application of controlled-release fertilizer did not significantlychange the crop yields, soil TN and TC content, and soil bacterial diversity.